Repetitive Transcranial Magnetic Stimulation in Psychiatric Disorders: A Review of Clinical Advances - Rashidi, Samaneh (Asian Journal of Pharmaceutics (AJP), 2017)
Psychiatric disorders are the most common debilitating diseases worldwide. Repetitive transcranial magnetic stimulation (rTMS) has shown therapeutic outcomes in different neurophysiology and neuropsychiatric disorders. Despite controversial findings on the therapeutic outcomes of this technique in different psychiatric disorders, researchers emphasize on developing this technique as an alternative or adjunctive modality for these disorders. Depression, different hallucinations, obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), and substance abuse are the main disorders have shown good treatment response to rTMS. This study aims to comprehensively overview the applications and recent advances in rTMS applications in psychiatric disorders. The databases of PubMed (1985-2017), Web of Sciences (1985-2017), Embase (1985-2017), Cochrane Central Library (1985-2017), and Google Scholar (1985-2017) were searched using the keywords of repetitive transcranial magnetic stimulation OR rTMS AND psychiatric disorders AND treatment. The retrieved records were reviewed, and the relevant studies were selected for further review. Repeated sessions of low frequency (â‰¤5 Hz) rTMS induce long-lasting neural inhibition or depotentiation, whereas high frequency (>5 Hz) induces long-lasting neural excitability or potentiation. Depending on the neural alteration induced by a disorder, low- or high-frequency rTMS is used for the treatment. The rTMS is approved as acute treatment for major depression. The other diseases with promising outcomes are different hallucinations, OCD, and PTSD. rTMS seems to be an alternative or adjunctive therapeutic modality in different psychiatric disorders. To reach efficient clinical application for each disorder, further randomized clinical trials, as well as preclinical studies, are needed.